2020
DOI: 10.1007/s42439-020-00031-0
|View full text |Cite
|
Sign up to set email alerts
|

A Quest for an Eco-centric Approach to International Law: the COVID-19 Pandemic as Game Changer

Abstract: This Reflection starts from the ongoing COVID-19 pandemic as unprecedented occasio to reflect on the approach to international law, which—it is contended—is anthropocentric, and its inadequacy to respond to current challenges. In the first part, the Reflection argues that there is, more than ever, an undeferrable need for a change of approach to international law toward ecocentrism, which puts the environment at the center and conceives the environment as us, including humans, non-human beings, and natural obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The pandemic that spread worldwide in 2020 has detrimentally impacted both human health and the environment (De Vido, 2020). It has been suggested that COVID-19 emerged as a result of humans living in an anthropocentric manner, with humans at the top of the hierarchy.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic that spread worldwide in 2020 has detrimentally impacted both human health and the environment (De Vido, 2020). It has been suggested that COVID-19 emerged as a result of humans living in an anthropocentric manner, with humans at the top of the hierarchy.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of law (justice) overlaps at this point with the issue of legal ontology. In this sense, the human formula and/or its part which regulates human behaviour in relation to other natural entities ("nomos interspecies") 47 is understood as the "correct path" 48 which ensures a harmonious centrality of human community in Nature.…”
Section: московский журнал международного права • 4 • 2021mentioning
confidence: 99%
“…47 For the purpose of transparency, for that part of the human formula which specifies the rules of behaviour with regard to other biotic communities, the term "nomos interspecies" or "law of Nature" will be used and for other parts of the human formula (the rules regulating man's private interaction and the rules regulating man's social interaction, i.e., man's social and/ or political thought, the term "internal law" will be used. 48 For understanding law as the "correct path" see [Fletcher 1996:38-39]. For general issues of legal ontology see [Posner 1990:161-247].…”
Section: московский журнал международного права • 4 • 2021mentioning
confidence: 99%
“…First, Earth law assumes that all of Nature (ecosystems and species, plants, microorganisms and animals, as well as biotic and abiotic components) have inherent and fundamental rights [ 17 ]. Earth law also assumes that humans exist as a part of Nature within an inextricable and complex web of relationships, and as a result, human rights are embedded within and dependent on the realization of Nature’s inherent rights [ 27 29 ]. Just as humans have rights based on our existence and being, so too does Nature.…”
Section: Introductionmentioning
confidence: 99%
“…Second, to date, environmental law has largely contributed to, and is unable to effectively react to, the growing environmental crisis. This is predominantly the result of a colonial worldview of humanity as separate from and owners of Nature, largely anthropocentric (human-centered) environmental laws and policies, and equating Nature to a resource and property with value derived from benefit and utility to humankind [ 20 , 27 , 30 – 34 ]. Although not all worldviews and legal frameworks adopt this paradigm, within this Essay, we use the vision for the Ocean Decade: “the science we need for the ocean we want,” as an example of international community norms and values that convey that humans are the primary beneficiary of a healthy Ocean [ 1 ].…”
Section: Introductionmentioning
confidence: 99%